2005
DOI: 10.1002/ejic.200401017
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Li+, Ca+, V+, and Cu+ to the Molecules S8 and S4 –A Computational Study

Abstract: Keywords: Ab initio calculations / S ligands / Cluster compounds / Lithium / Calcium / Vanadium / CopperThe complex formation between the Li + cation and the sulfur homocycle S 8 has been studied by ab initio MO calculations at the G3X(MP2) level of theory. Starting with various isomers of S 8 , the formation of LiS 8 heterocycles and clusters is preferred over complexes with a monodentate ligand. The binding energies of the cation in the 23 complexes investigated range from -95 to -217 kJ·mol -1 . The global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…On the other hand, quantum-mechanical calculations do suggest that sulfur can exist as a neutral ligand in a condensed phase. [42] Following these ideas, Krossing et al were able to obtain different metal-sulfur complexes, in particular with copper and silver as metal centers, by utilizing the mild reaction conditions and the presence of WCAs (see Section 3). As an approach to the synthesis, sonographic exposure of reaction mixtures of Ag[Al(OR F ) 4 ] (R F = C(CF 3 ) 3 , for example) and CuI or [Cu(1,2-F 2 C 6 H 4 ) 2 ][Al(OR F ) 4 ] in CS 2 and CH 2 Cl 2 with an excess of sulfur were chosen.…”
Section: Oxidizing Conditions: Chalcogen-rich and Halogen-rich Compoundsmentioning
confidence: 99%
“…On the other hand, quantum-mechanical calculations do suggest that sulfur can exist as a neutral ligand in a condensed phase. [42] Following these ideas, Krossing et al were able to obtain different metal-sulfur complexes, in particular with copper and silver as metal centers, by utilizing the mild reaction conditions and the presence of WCAs (see Section 3). As an approach to the synthesis, sonographic exposure of reaction mixtures of Ag[Al(OR F ) 4 ] (R F = C(CF 3 ) 3 , for example) and CuI or [Cu(1,2-F 2 C 6 H 4 ) 2 ][Al(OR F ) 4 ] in CS 2 and CH 2 Cl 2 with an excess of sulfur were chosen.…”
Section: Oxidizing Conditions: Chalcogen-rich and Halogen-rich Compoundsmentioning
confidence: 99%
“…21 and 22, respectively. Quantum chemistry calculations of structures and vibrational frequencies are also reported for VS n + , 15,17,18,23,24 V 2 S 2 + and V 3 S 4 + , 25 and VS and VS 2 . 22 In the present work, neutral V m S n clusters are produced and detected by MPI and SPI techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our previous work we have shown that the sulfur homocycles S 6 , [45] S 7 , [46] and S 8 [47] form chelate complexes of the type [MS n ] + with univalent metal cations such as Li + , Ca + , V + , and Cu + . The last three metal ions are even able to break down the S 8 molecule to form complexes with two S 4 ligands which are more stable than the isomeric S 8 complexes.…”
mentioning
confidence: 98%
“…The last three metal ions are even able to break down the S 8 molecule to form complexes with two S 4 ligands which are more stable than the isomeric S 8 complexes. [47] To reduce the calculation time for the zinc oxide adducts we substituted S 8 by the chairlike S 6 , which is also of high symmetry (D 3d ). [48] In the case of Li + the most stable complex with S 6 is of C 3v symmetry with a binding energy of À134 kJ mol…”
mentioning
confidence: 99%